Serum iron concentration and total iron binding capacity in patients of oral squamous cell carcinoma - Shakhawat Hossain, Motiur Rahman Molla and Mahmuda Akhter (Bangladesh Pharmacological Society, 2007)
The serum iron concentration and Total Iron Binding Capacity (TIBC) status of 24 patients of oral squamous cell carcinoma were compared with 13 healthy subjects. Biochemical evidence shows oral squamous cell carcinoma is found to have association with low serum iron level. More patients were found to be with significantly lower iron content in serum (p<0.05). But any association between serum TIBC and increased risk of cancer was not found (p>0.05). Irrespective of age, sex, smoking and betel nut chewing habit of subjects, low serum iron level significantly increase the risk of oral malignancy.